Estrategias económicas de los inmigrantes venezolanos en el centro histórico de Trujillo, 2021 - Marquina Cruz, Karina Jennifer (2022)
For this research: Economic Strategies of Venezuelan immigrants in the Historic Center- 2021. The research was developed with the aim of identifying what are the economic strategies of Venezuelan immigrants in the historic center-Trujillo in the year 2021. Much of the Venezuelan population has made the decision to emigrate to other countries, seeking economic stability that in their country seems foreign and unsustainable, a massive Venezuelan migration is looking for other places that offer them income and opportunities to start over, to survive from the evil government that your country suffers and give prompt help to the relatives who stayed behind. Men and women between 18 and 35 years of age, these same ones, who in Venezuela exercised a profession, currently find themselves in the need to look for new forms of work and trades such as cosmetology, outpatient commerce, attention in restaurants and sale of their traditional dishes. Most of the young Venezuelan immigrants are independent workers who do not have a formal job due to their immigration status and many of the young immigrants are illegal. Likewise, companies take advantage of their illegal status for them, to establish them in their companies, without recognizing all their benefits as a formal worker.